Perencanaan Enterprise Architecture pada Perusahaan Personal Care PT X - Lesmono, Stanley Utomo; Setiawan, Alexander; Gunawan, Ibnu (Jurnal Infra, 2015)
PT X is a company engaged in manufacturing personal care products. The company has used production information system to support their business process. A fraction of the business processes in PT X still has information system that is recorded manually. In this thesis, analysis and design of enterprise architecture for creating information systems to support the companyâs business process uses the framework of enterprise architecture planning. The first step begins with analyzing the business model and business strategy. The second step is observing the condition of information technology in company right now, what problems that have to be faced and the need of information technology in the future. The last step is designing data architecture, application architecture and technology architecture that is accordance with purpose, business strategy and business process in company. The results of the data architecture design are data entities and information sub-systems that exist in the company. The design of application architecture is application list. As for the technology architecture design using Client / Server Architecture, Message Bus and Service Oriented Architecture Pattern.